Joint Source Channel Decoding Exploiting 2D Source Correlation with Parameter Estimation for Image Transmission over Rayleigh Fading Channels - Mohd Nor, Muhamamd Izzat Amir; MOHD IZHAR, MOHD AZRI; Ahmad, Norulhusna; MAD KAIDI, HAZILAH (International Journal of Integrated Engineering, 2018)
This  paper  investigates  the  performance  of  a  2- Dimensional  (2D)  Joint  Source  Channel  Coding  (JSCC)  system assisted  with  parameter  estimation  for  2D  image  transmission over  an  Additive  White  Gaussian  Noise  (AWGN)  channel  and a  Rayleigh  fading  channel.  Baum-Welsh  Algorithm  (BWA)  is employed  in  the  proposed  2D  JSCC  system  to  estimate  the source correlation statistics during channel decoding. The source correlation is then exploited during channel decoding using a Modified Bahl-Cocke-Jelinek-Raviv (BCJR) algorithm. The performance of the 2D JSCC system with the BWA-based parameter estimation technique (2D-JSCC-PET1) is evaluated via image transmission simulations.  Two  images,  each  exhibits  strong  and weak  source  correlation  are  considered  in  the  evaluation  by measuring the Peak Signal Noise Ratio of the decoded images at the  receiver.  The proposed 2D-JSCC-PET1 system is compared with various benchmark systems. Simulation results reveal that the 2D-JSCC-PET1 system outperforms the other benchmark systems (performance gain of 4.23 dB over the 2D-JSCC-PET2 system and 6.10 dB over the 2D JSCC system).  The proposed system also can perform very close to the ideal 2D JSCC system relying on the assumption of perfect source correlation knowledge at the receiver that shown only 0.88 dB difference in performance gain.